2017
DOI: 10.1371/journal.pone.0181346
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin signaling pathway inhibits the proliferation and apoptosis of U87 glioma cells via different mechanisms

Abstract: The Wnt signaling pathway is necessary for the development of the central nervous system and is associated with tumorigenesis in various cancers. However, the mechanism of the Wnt signaling pathway in glioma cells has yet to be elucidated. Small-molecule Wnt modulators such as ICG-001 and AZD2858 were used to inhibit and stimulate the Wnt/β-catenin signaling pathway. Techniques including cell proliferation assay, colony formation assay, Matrigel cell invasion assay, cell cycle assay and Genechip microarray wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 49 publications
1
50
0
1
Order By: Relevance
“…Allen et al reported the origin of the U-87 MG cell line as mislabeled and unknown; they compared the original U-87MG cell line firstly identified at Uppsala University with the commercial U-87MG cell line from ATCC HTB 14TM. Genotyping analysis revealed that the ATCC and Uppsala U-87 MG cell lines were from distinct origins [ 57 ]; however, other recent studies [ 58 , 59 , 60 ] have demonstrated that the U-87MG ATCC cell line has several typical characteristics of glioblastoma through analyses of cell morphology and gene expression profile, even though the origin patient is unknown. Thus, U-87 MG can be used as a bonafide human glioblastoma cell line.…”
Section: Methodsmentioning
confidence: 99%
“…Allen et al reported the origin of the U-87 MG cell line as mislabeled and unknown; they compared the original U-87MG cell line firstly identified at Uppsala University with the commercial U-87MG cell line from ATCC HTB 14TM. Genotyping analysis revealed that the ATCC and Uppsala U-87 MG cell lines were from distinct origins [ 57 ]; however, other recent studies [ 58 , 59 , 60 ] have demonstrated that the U-87MG ATCC cell line has several typical characteristics of glioblastoma through analyses of cell morphology and gene expression profile, even though the origin patient is unknown. Thus, U-87 MG can be used as a bonafide human glioblastoma cell line.…”
Section: Methodsmentioning
confidence: 99%
“…36 Dysregulation of Wnt/β-catenin signaling has been identified as a vital pathogenesis of glioma development. 37 β-catenin is the crucial downstream regulator of the classic Wnt signaling pathway and overexpression of β-catenin is highly related to the progression of glioma. Inhibition of the Wnt/βcatenin signaling pathway thus represent a potential therapeutic approach for glioma.…”
Section: Discussionmentioning
confidence: 99%
“…В другом исследовании при подавлении отрицательного регулятора Wnt-каскада DKK1 с помощью ASCL1 (human achaete-scute homolog) Wnt-сигнальный путь в СКГ активировался [4]. Небольшие молекулымодуляторы Wnt ICG-001 и AZD2858 подавляли и активировали Wnt / β-катенин-каскад в клетках МГБ U87: ICG-001 ингибировал Wnt / β-катенин / TCF-зависимую транскрипцию генов в CBP-зависимой манере и снижал пролиферацию и клоногенный потенциал СКГ, а AZD2858 активировал транскрипцию генов через ингибирование GSK3β [62].…”
Section: обзорные статьиunclassified